Kebijakan Industrialisasi Bangladesh dalam Menarik Investasi Asing sebagai Dampak Kebijakan Neoliberalisme - Lucitania Rizky (TRANSBORDERS: International Relations Journal, 2020)
Bangladesh is one of the developing countries in South Asia that succed to implement industrialization policy to attract foreign direct investment in there. Political factors in Bangladesh have a very important role in determining neoliberal policies to support the economic development process. Neoliberalism policy here does not mean that the state does not support the economy. Market relations and market shifts require a state, or an agency related to the state, to discuss and protect private property and enforce contracts that are important features of market transition. In this case, the support of the Bangladeshi government in supporting the entry of investors is done by asking for such economic liberalization, privatization of state-owned entreprise, providing incentives to foreign investors and supporting with skilled labor and low wages. To accelerate the neoliberal policy agenda, the government of Bangladesh then undertook a integration process of national economic with the global economy, strengthened the role of the Bangladesh government in supporting neoliberalism policy, providing facilities for the movement of capital and labor and strengthened the corporate sector in industrialization policies in Bangladesh.